STUDI TENTANG SELF-CONCEPT AS A READER DAN VALUE OF READING MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI IKIP BUDI UTOMO MALANG - Mistianah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2017)
Reading is the active process of understanding print and graphic texts. Reading is a thinking process. Students use reading to acquire knowledge which is related to scholastic success. This study aims to describe about 1) students selfs concept as a reader; 2) students value of reading. Subjects in this study were students of an educational institute IKIP Budi Utomo Malang majoring in Biology Education Program. To measure students selfs concept and value of reading using MRP (Motivation to Read Profile) questionnaire. Reading motivations that consist of students selfs concept and value of reading from the respondents have been analyzed to find out how their reading motivations. The research found that 77,65% students thought that they were a good reader but 77,65% students answer that they just have few understand of what they read. Most of the students have a positive value of reading but only 55,29% students that use their half time to read. Based on the findings of a questionnaire-based survey, the paper also attempts to put forward recommendations for improving the reading motivation of students.